2020
DOI: 10.1097/adm.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Calls for Access to Safe Injecting Supplies as a Critical Public Health Measure During the COVID-19 Pandemic

Abstract: More than 3 decades of research has provided compelling evidence regarding the effectiveness, safety, and cost-effectiveness of needle and syringe programs in reducing syringe-sharing and transmission of HIV, HCV, and other bloodborne infections. However, repressive drug policies and drug law enforcement practices around the world continue to undermine their operations and scale-up, as well as access to harm reduction among people who inject drugs. The COVID-19 pandemic has heightened access barriers to needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The novel coronavirus (COVID-19) pandemic exacerbated multiple existing public health concerns and has significantly impacted people who use drugs (PWUD). Health leaders have called attention to the likelihood that isolation and psychosocial consequences of the pandemic may increase substance use, and that decreased access to substance use disorder (SUD) treatment and harm reduction services may increase transmission of drug use-related infections and worsen the overdose crisis [ 1 3 ]. Provisional data from the Centers for Disease Control and Prevention [ 4 , 5 ], emergency department records [ 6 , 7 ], and media reports from over 40 U.S. states [ 8 ] suggest that overdose deaths have risen sharply during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus (COVID-19) pandemic exacerbated multiple existing public health concerns and has significantly impacted people who use drugs (PWUD). Health leaders have called attention to the likelihood that isolation and psychosocial consequences of the pandemic may increase substance use, and that decreased access to substance use disorder (SUD) treatment and harm reduction services may increase transmission of drug use-related infections and worsen the overdose crisis [ 1 3 ]. Provisional data from the Centers for Disease Control and Prevention [ 4 , 5 ], emergency department records [ 6 , 7 ], and media reports from over 40 U.S. states [ 8 ] suggest that overdose deaths have risen sharply during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive assessment protocols were developed for people with OUD when they were treated in hospital for COVID-19 and efforts were made to provide and continue OUD treatment for them [ 5 , 19 ]. Maintaining the provision of needle and syringe programs is highlighted by several authors [ 20 ▪ , 21 , 22 ]. Mail-based needle and syringe distribution services, home delivery and vending machine were suggested as these measures provide increased accessibility for patients, no-contact service, and around-the-clock convenience [ 13 ▪▪ , 20 ▪ , 22 ].…”
Section: Responses and Strategies To Maintain Opioid Treatment Programs During The Pandemicmentioning
confidence: 99%
“…Table 3 shows the range of countries that the pieces of evidence were from. Continued unrestricted access to HR services, such as NSP (9), could be facilitated by ensuring an adequate supply of personal protective equipment (PPE) for staff (7,11,12).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Other authors also recommend vending machines, which provide 24-hour access, and no-contact collection (7,8). The LUCID-B study in Bristol reported positive feedback from PWID in relation to home delivery because it meant they did not have to travel, it kept them safe from COVID-19 and it prevented reuse of equipment (23).…”
Section: Nspmentioning
confidence: 99%
See 1 more Smart Citation